Krill og økosystemtokt med G.O.Sars i Sørishavet - Iversen, Svein A (Polaråret 2007-2008 : det norske bidraget, 2011)
Keywords: Bouvetøya; Det Internasjonale polaråret 2007; krill; marine økosystemer; plankton; polarforskning

Ecosystem study and krill survey aboard G.O. Sars in Southern Ocean - Iversen, Svein A; Coulthard, Alison (International Polar Year 2007-2008 : the Norwegian contribution, 2011)
Keywords: Bouvetøya; Det Internasjonale polaråret 2007; krill; marine økosystemer; plankton; polarforskning

Crustacea in Arctic and Antarctic Sea Ice: Distribution, Diet and Life History Strategies - Arndt, Carolin E.; Swadling, Kerrie M. (Advances in Marine Biology, 2006)
This review concerns crustaceans that associate with sea ice. Particular emphasis is placed on comparing and contrasting the Arctic and Antarctic sea ice habitats, and the subsequent influence of these environments on the life history strategies of the crustacean fauna. Sea ice is the dominant feature of both polar marine ecosystems, playing a central role in physical processes and providing an essential habitat for organisms ranging in size from viruses to whales. Similarities between the Arctic and Antarctic marine ecosystems include variable cover of sea ice over an annual cycle, a light regimen that can extend from months of total darkness to months of continuous light and a pronounced seasonality in primary production. Although there are many similarities, there are also major differences between the two regions: The Antarctic experiences greater seasonal change in its sea ice extent, much of the ice is over very deep water and more than 80% breaks out each year. In contrast, Arctic sea ice often covers comparatively shallow water, doubles in its extent on an annual cycle and the ice may persist for several decades. Crustaceans, particularly copepods and amphipods, are abundant in the sea ice zone at both poles, either living within the brine channel system of the ice‐crystal matrix or inhabiting the ice–water interface. Many species associate with ice for only a part of their life cycle, while others appear entirely dependent upon it for reproduction and development. Although similarities exist between the two faunas, many differences are emerging. Most notable are the much higher abundance and biomass of Antarctic copepods, the dominance of the Antarctic sea ice copepod fauna by calanoids, the high euphausiid biomass in Southern Ocean waters and the lack of any species that appear fully dependent on the ice. In the Arctic, the ice‐associated fauna is dominated by amphipods. Calanoid copepods are not tightly associated with the ice, while harpacticoids and cyclopoids are abundant. Euphausiids are nearly absent from the high Arctic. Life history strategies are variable, although reproductive cycles and life spans are generally longer than those for temperate congeners. Species at both poles tend to be opportunistic feeders and periods of diapause or other reductions in metabolic expenditure are not uncommon.
Keywords: Sørishavet; copepoder; crustacea; havis; krill; marin biologi; plankton; polarområdene; sjøis

Transport and transfer of organochlorines in the marine Norwegian Antarctic sector: field sampling programme during NARE 200/01 - Olsson, Kristina; Poltermann, Michael; Savinov, Vladimir; Vögele, Barbara; Kassobokova, Ksenia; Fransson, Agneta (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: NARE 2000/01; Sørishavet; marin biologi; oseanografi; plankton

Alternate Carbon Pathways at Lower Trophic Levels in the Antarctic Food Web - Hewes, Christopher D; Holm-Hansen, Osmund; Sakshaug, Egil (Antarctic Nutrient Cycles and Food Webs, 1985)
Keywords: Sørishavet; Weddellhavet; diatomeer; fytoplankton; krill; marin biologi; oseanografi; plankton

Corethron Criophilum Castracane: Its distribution and structure - Fryxell, Greta A; Hasle, Grethe Rytter (Biology of the Antarctic Seas IV, 1971)
Keywords: Sørishavet; fytoplankton; marinbiologi; plankton; planteplankton

Morphologic Variability in Fasciculated Diatoms as Exemplified by Thalassiosira Tumida (Janisch) Hasle, Comb. Nov - Hasle, Grethe Rytter; Heimdal, Berit R; Fryxell, Greta A (Biology of the Antarctic Seas IV, 1971)
Keywords: Sørishavet; Weddellhavet; alger; marinbiologi; oseanografi; plankton

On the Antarctic euphasiids from the "Norvegia" expeditions 1929-30 and 1930-31 - Rustad, Ditlef (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I, 1934)
Keywords: Antarktis; Norvegia ekspedisjoner; euphausider; forskning; hydrografi; krill; marin biologi; plankton; zoologi

Euphasiacea : with notes in their biogeography and development - Rustad, Ditlef (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume I, 1930)
Keywords: Bouvetøya; Norvegia ekspedisjonen; forskning; krepsdyr; krill; marin biologi; plankton; zoologi